Impact of Merger on Financial Performance of Commercial Banks in Nepal - Aryal, Binita; Sapkota, Pitambar (Journal of Interdisciplinary Studies, 2026)
This study attempts to analyze the effect of merger on financial performance of Nepalese commercial banks before and after merger. It employs both casual comparative and descriptive research design. As a sample there is taken three commercial banks and study is based on secondary data between the periods of 2012/13 - 2023/24 AD. Mean, standard deviation of comparatively pre-post-merger, Pearson correlation and paired sample t-test of before and after merger financial performance is substitutability tested using eight independent variable Return of Assets (ROA), Market per Share (MPS), Non-Performing Loan to total Ratio (NPL), Earning per Share (EPS), Return on equity (ROE), Cash to total deposit ratio (CDR), Net profit margin ratio (NPM), and Capital adequacy ratio (CDR). The analysis of impact of merger on financial performance of sample banks disclose ROA, MPS, NPL, EPS, ROE, NPM are decreased after the merger only CDR, and CAR increased after the merger. The CAR ratio of Siddhartha Banks seems to be significant improved after the merger. The NPM ratio of NIC Asia Banks has significantly decreased after the merger. In the case of Siddhartha Bank Limited it is found poor performance in ROA, ROE, EPS, and NPM after the merger. The study concludes that, merger is not proved as a significant tool to improve the financial performance of banks.